Meningkatkan Kualitas dan Kepercayaan: Pendampingan Keamanan Pangan untuk UMKM Kuliner - Krisnawati Setyaningrum Nugraheni; Dyah Palupiningtyas; Maria Corazon Lay Corbafo; Intan Aprillia Antaragiva (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
Food safety is a fundamental aspect in the culinary industry that plays a direct role in consumer health and business sustainability. However, culinary Micro, Small, and Medium Enterprises (MSMEs) often lack understanding of the importance of food safety standards and good sanitation practices. This community service activity aims to increase the awareness, knowledge, and skills of culinary MSME actors in implementing food safety principles as a whole. The methods used include theoretical and practical training, intensive assistance, and improvements to hygiene supporting facilities and infrastructure. A participatory and comprehensive approach is applied to ensure the active involvement of MSME partners in every stage of activities. This activity has significantly improved partner understanding, with pre-test and post-test scores showing an increase of 35%. As many as 90% of partners are able to demonstrate hygiene practices that meet standards, such as the use of personal protective equipment, raw material management, and sanitation of the work environment. In addition, the consumer satisfaction survey showed that 85% of respondents felt an improvement in the quality of culinary products after business actors implemented food safety principles. These results reflect the success of activities in forming a sustainable hygiene culture among culinary MSME actors. The holistic approach applied has proven to be effective in changing behavior and improving hygiene practices of business actors. This activity not only has an impact on improving product quality and consumer trust, but also strengthens the competitiveness of culinary MSMEs in a market that increasingly demands high quality standards. Thus, this community service makes a real contribution to strengthening the capacity of culinary MSMEs through the implementation of sustainable food safety.